Violence against women with mental disabilities: The invisible victims in CEE/NIS countries - Szeli Éva; Pallaska Dea (Temida)
In this paper, the authors are dealing with the problems that women with mental disabilities in Central and Eastern Europe, as well as in the Newly independent states have to face. In the conclusions, the recommendations indicating the direction of the future changes in the area are given.